Predictions for protection: A system to measure and detect asset bubbles - Singapore Management University (Institutional Knowledge at Singapore Management University, 2011)
The damage wrecked by the bursting of asset bubbles can have a devastating impact on investors' fortunes. In the Internet bubble, some US$8 trillion of shareholder wealth was destroyed. What is even more pertinent, however, is how the popping of a bubble can create a financial crisis, impacting nations and their economies. As a result, understanding how to identify bubbles is an important first step in combating these speculative bubbles, with interested parties ranging from the academic and investment community to central bankers and policy makers.